Chemical Composition and Antibacterial Activity of Bornean Medicinal Ginger Alpinia aquatica - Takashi Kamada; Shean, Yeaw Ng; Chin, Soon Phan; Charles S. Vairappan (2018)
One new phenylbutenoid, (3Z)-2',4',5'-trimethoxyphenylbutadiene (1) along with five known metabolites were isolated from aquatic galangal (Alpinia aquatica Rosc.) and their chemotaxonomy importance in five populations of A. aquatica collected from Kota Kinabalu, Ranau and Kota Belut in Sabah, Malaysia. The antibacterial potential as well as the chemosystematics importance of this discovery is discussed.